Aprovechamiento del glicerol producido en la industria de biodiésel en Colombia (2024)
The work focuses on exploring synthesis routes to transform glycerol, an abundant byproduct of the biodiesel industry, into more valuable products. Glycerol carbonate (CG) stands out for its industrial value, derived from a renewable raw material and with environmentally friendly properties. The most promising experimental works in the literature on this route do not present chemical kinetic information.